(untitled) (Abhat Journal, 2023)
This research dealt with the most prominent characteristics , features of collecting and notation of the holy Quran and I attempted to present the Topic from subtle Aspect to reach the desired benefit and they are as follows : summarizing the reasons For each combination and indicating its characteristics avoiding the researching Frequency and in order to reach the heart of the topic so the reader can reach it owing The full Idea about topic of collecting and notation the holy Quran which is Notated the Jamahiriya Mus’haf and studying that is Unique to it in drawing of In Jamahiriya Mus’haf which is the use special sign to delete the letter Alif And we will discuss the saying in details , its place and in Terms of the origin of Naming , purposes of its use and its reasons . This raised several questions from the specialists between the denier and the permissible Hoe ever we are nothing than we are researching this issue using the scientific research to remove the ignorance from our selves. perhaps someone who studies or researches Perhaps will find answer for his Questions and the most Important source that we have Resorted on the subject of Uniqueness of Jamahiriya Mus’haf ’ drawing with the sign of Deleting the letter Alif (allocated) are the scholars and the Sheikhs who learned in this Specialization and then Jamahiriya Mus’haf margin and the basic written source in this Aspect.